2015
DOI: 10.1111/bcpt.12386
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Spinal Bv8/Prokineticin 2 in a Rat Model of Cancer‐Induced Bone Pain

Abstract: Cancer-induced bone pain (CIBP) is seriously disruptive to the quality of life in cancer patients, and present therapies are limited. The Bv8/prokineticin 2, a new family of chemokines, has been demonstrated to be involved in inflammatory and neuropathic pain. However, whether it is involved in CIBP remains unclear. This study was designed to examine whether spinal Bv8 was involved in the development of CIBP in rats. A rat CIBP model was constructed by injecting Walker 256 carcinoma cells into the medullary ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Although, this model involving ITI of Walker 256 cells in rats might not exactly mimic the metastatic spread of breast cancer to the axial skeleton in humans (Kurth et al, 2001, 2002), it provides great insights into the pathobiology and mechanisms of breast CIBP and is hence used very widely in experimental research (Du et al, 2015; Hang et al, 2015; Hu S. et al, 2015; Liu et al, 2015; Lu et al, 2015). Undoubtedly, it is one of the most suitable preclinical models for efficacy assessment of novel compounds from discovery programs aimed at identifying drugs with potential to alleviate breast CIBP in humans.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, this model involving ITI of Walker 256 cells in rats might not exactly mimic the metastatic spread of breast cancer to the axial skeleton in humans (Kurth et al, 2001, 2002), it provides great insights into the pathobiology and mechanisms of breast CIBP and is hence used very widely in experimental research (Du et al, 2015; Hang et al, 2015; Hu S. et al, 2015; Liu et al, 2015; Lu et al, 2015). Undoubtedly, it is one of the most suitable preclinical models for efficacy assessment of novel compounds from discovery programs aimed at identifying drugs with potential to alleviate breast CIBP in humans.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to being a reproducible method for inducing skeletal metastasis (Blouin et al, 2005; Mao-Ying et al, 2006; Badraoui et al, 2009), this model mimics key features of human breast CIBP, including pharmacological profile (Mao-Ying et al, 2006, 2012; Cao et al, 2010). Walker 256 cells can be used in a variety of rat strains (Hang et al, 2015; Lu et al, 2015) because these cells produce uniformly rapid growth, show very little regression, and are readily adaptable (Lewis et al, 2013; Oliveira and Gomes-Marcondes, 2016). …”
Section: Suitability Of Walker 256 Cellsmentioning
confidence: 99%
“…The features of any given animal model of CIBP thus require characterisation using standardized protocols to reduce the number of variables affecting the experiments to enhance experimental reproducibility. In the present work, W256 cells were selected as they are widely used in research (Justice, 1985; Brigatte et al, 2007) and because of the ease with which they can be cultured, standardized and reproduced (McEuen and Thomson, 1933; Hang et al, 2015). A comparative summary of previous studies using the W256 cell-induced bone pain model in rats, has been comprehensively provided in a recent review (Shenoy et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Cancer-induced bone pain seriously impairs the quality of life of cancer patients; however, there are currently no effective therapies available for bone pain (29). In the present study, the mRNA expression levels of MCP-1 and its receptor CCR2 were found to be upregulated in the spinal cord of MTBP rats (BM group).…”
Section: Discussionmentioning
confidence: 99%